Purification of antibiotics from the millet extract using hybrid molecularly imprinted polymers based on deep eutectic solvents. Issue 28 (17th March 2017) - Li, Xiaoxia; Row, Kyung Ho
Abstract : Deep eutectic solvents (DESs) are potential ecofriendly surfactants for the preparation of molecularly imprinted polymers (MIPs). Abstract : Deep eutectic solvents (DESs) are potential ecofriendly surfactants for the preparation of various materials. In this study, molecularly imprinted polymers (MIPs) were modified by betaine-based DESs. These materials were characterized by field emission scanning electron microscope and Fourier transform infrared spectroscopy. The molecular recognition capability for antibiotics of materials was evaluated by static absorption and dynamic adsorption curves. Five materials were used as solid phase extraction (SPE) adsorbents for the rapid purification of levofloxacin and tetracycline from the millet extract. The DES-based materials showed more selective adsorption than the conventional MIPs. The adsorption curves of DES-MIP showed superior molecular recognition ability and binding capability for antibiotics than the other materials. The limit of detection and the limit of quantitation of the method for levofloxacin were 0.01 μg mL −1 and 0.03 μg mL −1, respectively. The method recoveries ranged from 97.2–100.2% for levofloxacin with DES-LMIP and 95.7–99.2% for tetracycline with DES-TMIP. DES-LMIP and DES-TMIP showed the highest selectivity recovery for levofloxacin (94.5%) and tetracycline (93.3%) from millet extract with mixture antibiotics, and could remove the interferent effectively.